REAKSI PASAR ATAS VARIABEL MAKRO DAN PROFITABILITAS: KAJIAN PERUSAHAAN DI BURSA EFEK INDONESIA TERKATEGORI DEVENSIFE DAN CYCLICAL INDUSTRY - Nur Fadjrih Asyik (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
This study examines the influence of macro variables and profitability to the market reaction to the companies listed in Indonesia Stock Exchange categorized as a defensive industry and cyclical industry. Independent variables in this study are macro variables which consists of inflation (I) and the interest rate (SB) and profitability ratios which consists of return on assets (ROA), return on equity (ROE), gross profit margin (GPM), net profit margin (NPM), as well as the dependent variable is stock returns (RS). Data obtained from ICMD (Indonesian Capital Market Directory), Indonesian Stock Exchange, JSX Monthly, and www.bi.go.id. Objects used in this study were food-beverage industry as a defensive industry and the automotive industry as a cyclical industry in 2007 through 2009. The results showed that the F value is 4.032 with probability value of 0.001, thus statistically significant at 1%. It can be concluded that the macro variables, profitability, and the type of industry (defensive industry and cyclical industry) together have a significant effect on stock returns of manufacturing firms listed on the Indonesia Stock Exchange. Partial coefficient of inflation, interest rates, ROE, GPM, NPM, and the type of industry are 2.695, -4.085, -0.711, -0.616, 0.391, and 0.301 with  p-value of 0.002, 0.006, 0.000, 0.033, 0.014, and 0.044 thus statistically significant at the 1% and 5%, thus concluded that the inflation, interest rates, ROE, GPM, NPM, and the types of industries have a significant effect on stock returns of manufacturing firms. Only the ROA variables that do not support the hypothesis.